Penguatan Ekonomi Kreatif pada UMKM di Desa Turunrejo Melalui Sosialisasi Strategi Pemasaran di Era Digital - Eka Dewi Fitriana; Ami Nurafni; Diniyati Rahmah; Amallia Lathifa Anfasa; Amelia Rosa Revina Yamani; Teguh Wibowo (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
Marketing strategies in the digital era are an important point for UMKM actors to market products both offline and online by utilizing social media platforms. The purpose of this socialization is to provide education about the importance of marketing strategies in the digital era and increase the marketing of UMKM products in a wider range. The method used is qualitative descriptive to explore information in depth about the topic of service. Activities include lectures, discussions, and outputs in the form of making pamphlets and mapping google maps. As a result of the implementation of this socialization, there is an increase in the reach of product marketing more widely through the distribution of pamphlets on social media and mapping of business locations on google maps. This activity succeeded in increasing participants' awareness of digital marketing strategies and providing insights into the use of social media to build branding for UMKM.